Financing the green transition: The role of private capital - Tabea Bucher-Koenen; Anna-Lena Herforth; Karolin Kirschenmann; Monireh Ravanbakhshhabibabadi (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
The greening of the European economy will require large amounts of capital to flow into green projects. As the public sector alone will not be able to achieve this, European capital markets and the European banking system will play an important role in financ- ing the green transition. In this policy brief, we provide evidence on the drivers and barriers for private and institutional inves- tors to engage in financing the green transition from two recent projects funded by the German Federal Ministry of Education and Research (BMBF) and the ZEW Sponsors' Association, respectively. For private investors, increasing (sustainable) financial lit- eracy is crucial to increase the capital market participation of EU households in general and sustainable investments in particu- lar. Furthermore, reliable and accessible information on sustainable financial products is important to facilitate retail investors' decisions to invest in green projects. For institutional investors, engagement and the integration of sustainability as an integral part of investment decisions seem to be the most promising ways to effectively create impact. For securitization to become a more attractive tool for financing the transition, it should be placed on a level regulatory playing field with other financial prod- ucts with similar risks. And while the new disclosure regulations impose high costs, their impact on sustainability remains un- clear. Overall, policymakers should focus on effective climate policies in the real economy and enabling regulatory frameworks for the financial sector.
Keywords: 330